Masjid, Khutbah Jumat, dan Konstruksi Realitas Keagamaan di Ruang Publik: Studi tentang Materi Khutbah Jumat di Masjid-Masjid Kota Surakarta - Mibtadin, Mibtadin; Hedi, Fathol (Jurnal Ilmu Dakwah, 2020)
This research is about the material or sermons content in Surakarta mosques in which there is an indication of hate speech if it is viewed from the analysis discourse and its implications for the religious diversity of worshipers in each mosque. Is there an element of hate speech in sermons in several mosques in the city of Surakarta? what are the implications of the Friday sermon on the diversity of society? This research is a descriptive qualitative research, data collection is done by observation, in-depth interviews, and documentation. Data analysis was performed with interactive analysis including: data reduction, data delivery; and drawing conclusions. Sermons are words that contain religious advice and information. Sermon material serves to strengthen the religious narrative of pilgrims. In general, the Friday sermon material does not contain indications of hate speech. The implication of Friday sermons on worshipers is to provide perspective and point of view so that it will affect the religious life of worshipers so they can be tolerant and respectful to groups outside of themselves.Â Penelitian ini mengenai materi atau konten khutbah yang ada di masjid-masjid Surakarta didalamnya ada indikasi mengandung unsur ujaran kebencian jika dilihat dari diskursus analisis serta implikasinya terhadap keberagamaan jamaah di setiap masjid. Apakah ada unsur ujaran kebencian pada khutbah di beberapa masjid a di Kota Surakarta? bagaimana implikasi khutbah Jumat terhadap keberagamaan masyarakat? Penelitian ini merupakan penelitian kualitatif deskriptif, pengumpulan data dilakukan dengan observasi, wawancara mendalam, dan dokumentasi. Analisis data dilakukan dengan interaktif analisis meliputi: reduksi data, penyampaian data; dan penarikan kesimpulan. Khutbah merupakan perkataan yang mengandung nasehat dan informasi keagamaan. Materi khutbah berfungsi untuk penguatan narasi keagamaan jamaah. Secara umum, materi khutbah Jumat yang ada tidak mengandung indikasi ujaran kebencian. Implikasi khutbah Jumat pada jamaah adalah memberikan perspektif dan cara pandang sehingga akan berpengaruh terhadap kehidupan beragama jamaah sehingga bisa bersikap toleran dan menghargai kepada kelompok di luar dirinya.